SISTEM JARINGAN DAN SIMPUL ANTARMODATRANSPORTASIDI KABUPATEN NABIRE - Hendra Pasu Parningotan Simanjuntak (Fakultas Teknologi dan Rekayasa, 2018)
The aims of this study are to: (1) explain the characteristics of inter-modal network system in Nabire; (2) analyze the demand for inter-modal nodes in Nabire regency; and (3) find out the concept of inter-modal network system development and inter-modal nodes in Nabire.The method used in this study was descriptive method with qualitative and quantitative analyses. The data were collected by using observation. The results reveal that, firstly, the characteristic of inter-modal transportation system network is still relatively limited; some areas are not yet connetted with road network. Secondly, the demand for transportation nodes occur in tree districts: Wanggar, Makimi, and Uwapa District. It is determined because the areas are the field of urban development, platation, agriculture, mining, and marine culture.That function to connect the villages that have the potentiality to be production centers; Trirdly, the development of inter-modal network system is conducted with: the contruction of unstructured road that connectecs the centers of sosio-economic activities in each district; the improvement of road based on the servis status; and the development of alternative routes as the city ring road. Next, the concept of inter-modal transportation node development includes: the regional terminal located in Nabire subdistrict as the meeting point of northern and mid cross traffic of trans-Papua road network (which server as the gateway to Dogiyai and Paniai regencies).